(3200) Phaethon polarimetry in the negative branch: new evidence for the anhydrous nature of the DESTINY+ target asteroid. Issue 1 (11th July 2022) - Geem, Jooyeon; Ishiguro, Masateru; Takahashi, Jun; Akitaya, Hiroshi; Kawabata, Koji S; Nakaoka, Tatsuya; Imazawa, Ryo; Mori, Fumiki; Jin, Sunho; Bach, Yoonsoo P; Jo, Hangbin; Kuroda, Daisuke; et al.
ABSTRACT: We report on the first polarimetric study of (3200) Phaethon, the target of JAXA's DESTINY + mission, in the negative branch to ensure its anhydrous nature and to derive an accurate geometric albedo. We conducted observations at low phase angles (Sun-target-observer angle, α = 8.8–32.4°) from 2021 October to 2022 January and found that Phaethon has a minimum polarization degree P min = −1.3 ± 0.1 per cent, a polarimetric slope h = 0.22 ± 0.02 per cent deg −1, and an inversion angle α0 = 19.9 ± 0.3°. The derived geometric albedo is p V = 0.11 (in the range of 0.08–0.13). These polarimetric properties are consistent with anhydrous chondrites, contradict hydrous chondrites, and typical cometary nuclei.